Computation of Phonon Density of States, Atomic Electrostatic Potential and Electric Field Gradient Tensor Using Single Crystal Data of Six Benzene Sulfonamide Based Compounds (Bulletin of Pure and Applied Sciences – Physics, 2022)
Molecular dynamic study of benzene sulfonamide based compounds was carried out  to compute several properties like phonon density of states, atomic electric potential  and electric field gradient tensor components and then compared. This work  establishes the correlation between physical properties and the quantity of carbon  atoms in a molecule. The GULP program was used to do all the calculations and  reported single crystal data.